Impact of the Electron Acceptor Nature on the Durability and Nanomorphological Stability of Bulk Heterojunction Active Layers for Organic Solar Cells - Vohra, Varun; Matsunaga, Yumi; Takada, Tomoaki; Kiyokawa, Ayumu; Barba, Luisa; Porzio, William (Small, 2021)
A systematic study is conducted to compare the performances and stability of active layers employing a high performance electron donor (PBDB‐T) combined with state‐of‐the‐art fullerene (PC71BM), nonfullerene (ITIC), and polymer (N2200) electron acceptors. The impact of the chemical nature of the acceptor on the durability of organic solar cells (OSCs) is elucidated by monitoring their photovoltaic performances under light exposure or dark conditions in the presence of oxygen. PC71BM molecules exhibit a higher resistance toward oxidation compared to nonfullerene acceptors. Unencapsulated PBDB‐T:PC71BM OSCs display relatively stable performances at room temperature when stored in air for 3 months. However, when exposed to temperatures above 80 °C, their active materials demix causing notable reductions in the short‐circuit densities. Such detrimental demixing can also be seen for PBDB‐T:ITIC active layers above 120 °C. Although N2200 chains irreversibly degrade when exposed to air, thermally induced demixing does not occur in PBDB‐T:N2200 active layers annealed up to 200 °C. In summary, fullerene OSCs may be the best currently available choice for unencapsulated room temperature applications but if oxidation of the polymer acceptors can be avoided, all polymer active layers should enable the fabrication of highly durable OSCs with lifetimes matching the requirements for OSC commercialization. Two degradation patterns are found for nonfullerene acceptors: small molecules like ITIC undergo a light‐mediated reversible degradation related to oxygen‐doping while polymer acceptors (N2200) are subject to permanent damage. Nevertheless, the chemical compatibility between the electron donor (PBDB‐T) and nonfullerene polymer acceptors results in an unprecedented morphological stability up to 200 °C.